Re‐emergent tremor in Parkinson's disease: the effect of dopaminergic treatment. (6th April 2018) - Belvisi, D.; Conte, A.; Cutrona, C.; Costanzo, M.; Ferrazzano, G.; Fabbrini, G.; Berardelli, A.
Abstract : Background and purpose: Patients with Parkinson's disease (PD) with resting tremor may be affected by a tremor that appears after a varying latency while a posture is maintained, a phenomenon referred to as re‐emergent tremor (RET). The aim of the study was to evaluate the occurrence and clinical features of RET in patients with PD tested off and on treatment, and to compare the effect of dopaminergic treatment on RET with the effect on resting and action tremor. Methods: We consecutively enrolled 100 patients with PD. Patients were clinically evaluated 24 h after withdrawal of therapy (off‐treatment phase) and 60 min after therapy administration (on‐treatment phase). We collected the demographic and clinical data of patients with PD. The severity of the disease was assessed by means of the Hoehn and Yahr scale and Movement Disorder Society‐sponsored revision of the Unified Parkinson's Disease Rating Scale part III. We evaluated the latency, severity and body side affected both off and on treatment in patients with RET. Results: Re‐emergent tremor was present in 24% of the patients with PD off treatment and in 19% of the patients on treatment. Dopaminergic treatment reduced the clinical severity of RET. Dopaminergic treatment increased the number of patients with unilateral RET and reduced the number of those who had bilateral RET. RET and resting tremor responded similarly to dopaminergic treatment, whereas action tremor was less responsive. Patients with RET had milder motor symptoms than patients without RET both off and on treatment. Conclusions: Dopaminergic treatment modified RET occurrence, severity and body distribution. Dopaminergic depletion plays a role in the pathophysiology of RET. Abstract : Clickhere for the corresponding questions to this CME article.